2018
DOI: 10.1002/msc.1234
|View full text |Cite
|
Sign up to set email alerts
|

Measuring person‐centred care in nurse‐led outpatient rheumatology clinics

Abstract: We found general support for the appropriateness of the PCCoc/rheum as an outcome measure of patient-perceived PCC in nurse-led outpatient rheumatology clinics. While in need of further testing, the 21-item PCCoc/rheum has the potential to evaluate outpatient PCC from a patient perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…According to the quality of care δ values, the items originating from the subscales respect and integrity and information and knowledge were considered as easier to satisfy and the items originating from the subscales planning and decision making and motivation and encouragement were considered as more difficult to satisfy (Table ). This could be considered, qualitatively and when comparing to other scales, as creating successful hierarchical rulers. Despite some minor misfits and significant item‐trait interaction chi‐square tests ( P < 0.001), the cumulated fit statistics showed that the PPRQ‐17 acceptably satisfies the RMT (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the quality of care δ values, the items originating from the subscales respect and integrity and information and knowledge were considered as easier to satisfy and the items originating from the subscales planning and decision making and motivation and encouragement were considered as more difficult to satisfy (Table ). This could be considered, qualitatively and when comparing to other scales, as creating successful hierarchical rulers. Despite some minor misfits and significant item‐trait interaction chi‐square tests ( P < 0.001), the cumulated fit statistics showed that the PPRQ‐17 acceptably satisfies the RMT (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the content of PPRQ seems to corroborate a broader patient perspective; the understanding of staff; theories of PCC; and other similar questionnaires . However, recent Rasch validations of two other similar questionnaires, the Patient Preference for Patient Participation tool (The 4Ps) and Person‐Centered Care in outpatient care in rheumatology (PCCoc/rheum), suggest a unidimensionality for similar subcomponents as the PPRQ. Likewise, previous studies of the PPRQ using CTT revealed high correlations between the subscales, indicating a potential full scale for patient participation.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…This is a relatively common problem for this type of measure. For example, in a study of person-centered care (in which participation in care is an underlying concept) in nurse-led outpatient rheumatology clinics, there was also poor targeting of the scale for those experiencing higher levels of person-centered care [71]. If the goal is to examine people experiencing a very high level of participation in greater detail, with less error, it may be necessary to add more items at the end of the scale.…”
Section: Communication and Trustmentioning
confidence: 99%